Finding Meaning Amidst COVID-19: An Existential Positive Psychology Model of Suffering - Van Tongeren, Daryl R.; Showalter Van Tongeren, Sara A. (Frontiers in Psychology, 2021)
The global COVID-19 pandemic has created a crisis of suffering. We conceptualize suffering as a deeply existential issue that fundamentally changes people indelible ways and for which there are no easy solutions. To better understand its effects and how people can flourish in the midst of this crisis, we formally introduce and elaborate on an Existential Positive Psychology Model of Suffering (EPPMS) and apply that to the COVID-19 global pandemic. Our model has three core propositions: (a) suffering reveals existential concerns, (b) existential anxiety impairs one’s ability to find meaning, and (c) cultivating meaning is the primary way to address suffering and allay existential anxiety, eventually leading to flourishing (and potentially growth). We apply this model to the COVID-19 pandemic, including how to build meaning, and discuss clinical implications.